2009
DOI: 10.1007/978-3-642-00576-3_19
|View full text |Cite
|
Sign up to set email alerts
|

Disk-Magnetosphere Interaction and Outflows: Conical Winds and Axial Jets

Abstract: We investigate outflows from the disk-magnetosphere boundary of rotating magnetized stars in cases where the magnetic field of a star is bunched into an X-type configuration using axisymmetric and full 3D MHD simulations. Such configuration appears if viscosity in the disk is larger than diffusivity, or if the accretion rate in the disk is enhanced. Conical outflows flow from the inner edge of the disk to a narrow shell with an opening angle 30-45 degrees. Outflows carry 0.1-0.3 of the disk mass and part of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…Machida et al 2006;Hawley 2009;Romanova et al 2009;Mignone et al 2010, and references therein) have apparently shown that jet formation and acceleration is due to one of two types of physical mechanisms: plasma gun/magnetic towers, as proposed by Contopoulos (1995)/Lynden-Bell (1996, or centrifugal driving, as proposed by Blandford & Payne (1982). What is most important, however, is that these simulations demostrate that at the origin of jet formation and acceleration lies a large-scale magnetic field that threads the central "driving engine" (the central compact object and the surrounding innermost accretion disk).…”
Section: Jet Formation and Destructionmentioning
confidence: 99%
“…Machida et al 2006;Hawley 2009;Romanova et al 2009;Mignone et al 2010, and references therein) have apparently shown that jet formation and acceleration is due to one of two types of physical mechanisms: plasma gun/magnetic towers, as proposed by Contopoulos (1995)/Lynden-Bell (1996, or centrifugal driving, as proposed by Blandford & Payne (1982). What is most important, however, is that these simulations demostrate that at the origin of jet formation and acceleration lies a large-scale magnetic field that threads the central "driving engine" (the central compact object and the surrounding innermost accretion disk).…”
Section: Jet Formation and Destructionmentioning
confidence: 99%
“…Three-dimensional magnetohydrodynamic simulations (Machida et al 2006;Hawley 2009;Romanova et al 2009;Mignone et al 2010) have shown that there are two mechanisms for jet formation, both requiring a strong large-scale magnetic field: plasma gun/magnetic tower (Contopoulos 1995;LyndenBell 1996), and centrifugal driving (Blandford & Payne 1982). Such a magnetic field can originate from a large distance and the advecting flow carries it to the inner region and amplifies it (Igumenshchev 2008;Lovelace et al 2009;Tchekhovskoy et al 2011).…”
Section: Quiescent Statementioning
confidence: 99%
“…On average, FUor outbursts should occur (or recur) about five times per star formed in the local region of the Milky Way (Hartmann & Kenyon 1996); there have been ∼10 FUors observed within a distance of 1.5 kpc in the last 80 years, compared with the star-formation rate in the same volume (about three per 50 years). These bursts also modify the protoplanetary disk chemistry and require a very different model than simple magnetospheric accretion (e.g., Green et al 2006;Quanz et al 2007;Zhu et al 2007;Romanova et al 2009;Cieza et al 2016), usually invoked for accreting young stars. If FUors represent a short-duration stage that all young stars undergo, then understanding their properties is vital to models of planet formation and the evolution of protoplanetary gas-rich disks.…”
Section: Introductionmentioning
confidence: 99%